Well Being and Conservation Awareness of Communities around Chitwan National Park, Nepal - Jhala, Harshini Y.; Pokheral, Chiranjibi Prasad; Subedi, Naresh (Indian Forester, 2019)
Biodiversity conservation especially in Protected Areas (PA) depends on Community Based Conservation (CBC) programs. Sharing of PA revenues with local communities in the buffer zone of PA’s is a major component of CBC. Herein, we assess the effectiveness of the CBC programs in Chitwan National Park, Nepal by evaluating people’s perception of benefits shared from PA with the existence of the PA. The communities around Chitwan were found to be economically well off compared to national averages, majority (71%) had concrete houses, with all households having electricity and water supply. Majority (79%) of the people were aware of park revenue being shared and 73.6% linked community welfare works to the existence of the PA. Most people (55%) were aware of ecological concepts like impacts of deforestation and loss of large carnivores. We found no differences amongst the respondents based on gender, economic strata or educational levels in their responses. Park management would benefit by focusing on awareness campaigns that link shared benefits to existence of the PA and streamlining payment of compensation for crop and livestock damage by wildlife.